A review of phytoplankton dynamics in tropical African lakes - Mzime Ndebele-Murisa; Charles Musil; Lincoln Raitt (South African Journal of Science)
This paper provides a synthesis of current knowledge on phytoplankton production, seasonality, and stratification in tropical African lakes and considers the effects of nutrient enrichment and the potential impacts of climate warming on phytoplankton production and composition. Tropical African lakes are especially sensitive to climate warming as they experience wide fluctuations in the thermocline over a narrow range of high water temperatures. Recent climate warming has reduced phytoplankton biomass and production in the lakes. A decline in the production of palatable chlorophytes and an increase in cyanobacteria has led to reduced zooplankton production and a consequent decline in fish stocks, all of which can be associated with the elevated water temperatures. This indicates that even moderate climate warming may destabilise phytoplankton dynamics in tropical African lakes, thereby reducing water quality and food resources for planktivorous fish, with consequent negative impacts on human livelihoods.